2018
DOI: 10.1002/pds.4406
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use and the risk of fractures among an older adult cohort

Abstract: No association was observed between PPI use and fracture risk among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
(64 reference statements)
1
19
0
1
Order By: Relevance
“…2 Second, previous research has suggested that no significant association can be detected between proton pump inhibitors therapy and fracture risk in older adults. 4 Ozen et al's and our studies further confirm that even in patients with rheumatoid arthritis, such an association still does not exist. Third, I agree with Sugiyama's comments published in the Annals of the Rheumatic Diseases reporting that no conclusive evidence supports a cause-effect relationship between proton pump inhibitors therapy and fracture risk, regardless of the population studied.…”
supporting
confidence: 84%
“…2 Second, previous research has suggested that no significant association can be detected between proton pump inhibitors therapy and fracture risk in older adults. 4 Ozen et al's and our studies further confirm that even in patients with rheumatoid arthritis, such an association still does not exist. Third, I agree with Sugiyama's comments published in the Annals of the Rheumatic Diseases reporting that no conclusive evidence supports a cause-effect relationship between proton pump inhibitors therapy and fracture risk, regardless of the population studied.…”
supporting
confidence: 84%
“…Fracture risk in the general population using PPIs, such as children, young adults, men, elderly, and postmenopausal women, was explored in several studies [30,31,32,33,34,35,36,37,38,39,40,41,42]. In the case-control study of Freedberg et al involving children (4–17 years; n = 87,071; 69.8% were cases) and young adults (18–29 years; n = 37,728; 30.2% were cases) in the United States (follow-up period: five years), a positive relationship between fracture risk and PPI exposure in young adults was found, with a body mass index (BMI)-adjusted odds ratio (aOR) of 1.39 (95% confidence interval (CI): 1.26–1.53) [41].…”
Section: The Relationship Between Ppis and Fracture Riskmentioning
confidence: 99%
“…Moreover, use of PPIs may also increase risk of falls [ 291 , 292 , 293 ]. These associations, however, have not been confirmed in a number of longitudinal studies and reviews [ 259 , 280 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 ]; even a modest reduction in fracture risk with PPI use has been reported [ 307 , 310 ]. Some researchers who are not supporting the association of PPI therapy with BMD recognize, nevertheless, that in PPI users the risk of fractures and falls could be higher [ 311 , 312 ] as the unadjusted HR was significantly elevated (1.36, 95% CI 1.19–1.55).…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%